2010
DOI: 10.1200/jco.2009.26.9944
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Mesothelin-Related Peptide and Osteopontin As Markers of Response in Malignant Mesothelioma

Abstract: Percentage changes in SMRP levels, but not changes in OP levels, are a potentially useful marker of disease course. These findings should be validated prospectively for a role as an objective adjunctive measure of disease course in both clinical trials and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
78
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 15 publications
13
78
0
Order By: Relevance
“…A significant association was observed between the response outcome and the relative change in mesothelin levels in 21 patients receiving chemotherapy [37]. This was further supported by CREANEY et al [38], who demonstrated that a decrease in serum mesothelin levels following chemotherapy increases the likelihood that the tumour is responding to therapy and that it also predicts for improved survival independent of age, sex, histology and treatment.…”
Section: Treatment Monitoring Performancesupporting
confidence: 66%
See 2 more Smart Citations
“…A significant association was observed between the response outcome and the relative change in mesothelin levels in 21 patients receiving chemotherapy [37]. This was further supported by CREANEY et al [38], who demonstrated that a decrease in serum mesothelin levels following chemotherapy increases the likelihood that the tumour is responding to therapy and that it also predicts for improved survival independent of age, sex, histology and treatment.…”
Section: Treatment Monitoring Performancesupporting
confidence: 66%
“…Mesothelin levels fall with tumour resection and rise with its progression [17]. Measurement of mesothelin may be useful in monitoring treatment response [26,[35][36][37]. Two recent studies suggested that a 10% change in mesothelin levels above baseline values is significant [36,37], whereas others proposed a threshold of 25% [38].…”
Section: Treatment Monitoring Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported increased SMRP to be an independent prognostic factors for mesothelioma, with mesothelin levels negatively correlating with survival 31,36,37,63,71,74 . Another area of application of serum mesothelin measurement is monitoring of mesothelioma progression and its response to therapy, with SMRP being increased in disease progression and stable or decreasing SMRP levels being a sign of positive response to therapy 30,53,63,64,70,71,79 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (8)(9)(10)(11)(12)(13)(14) confirmed that serum SMRP was a promising marker for diagnosis, prognosis and clinical monitoring of MPM. High SMRP concentrations were detected in all the studies only in the epithelioid and mixed MPM.…”
Section: Soluble Mesothelin-related Peptides (Smrp)mentioning
confidence: 87%